I Don't Even Recognize You Anymore - Niedersüß, Carl Dominik J. (Nomos Verlagsgesellschaft mbH & Co. KG, 2021)
Traditional trade marks have become a rarity, widely replaced by more appealing means of market communication. Fueled by the CJEU's liberal jurisdiction, widening the subject matter eligible for trade mark protection, a whole new world of opportunity has opened up to advertisers.